'You can't see for lookin'': how southern womanism informs perspectives of work and curriculum theory - Morton, Berlisha (Gender and education, 2016)
Southern womanism is the theory that evokes a self-reflexive process to challenge scholars, teachers, and activists to reconceptualise the agency of 'workers.' Southern womanism claims that theoretical knowledge resides within the histories of southern Black women workers which developed as they transitioned from enslavement to domestic work to birthing a generation of African ascendant scholars and artists. Within their work is the theoretical possibility of exploring these women as agential subjects whose intellectual history is found in the intersections of region, regional identity, race, gender, sexuality, nature, art, food, and spirituality.